Peripheral innate and adaptive immune cells during COVID-19: Functional neutrophils, pro-inflammatory monocytes, and half-dead lymphocytes - SİLİ, ULUHAN (WILEY, 2021)
Background A better understanding of innate and adaptive cells in COVID-19 is necessary for the development of effective treatment methods and vaccines. Methods We studied phenotypic features of innate and adaptive immune cells, oxidative burst, phagocytosis, and apoptosis. One hundred and three patients with COVID-19 were grouped according to their clinical features into the categories of mild (35%), moderate (40.8%), and severe (24.3%). Results Monocytes were CD16(+) pro-inflammatory monocytes and tended to shed their HLA-DR, especially in severe cases (p < 0.01). Neutrophils were mature and functional, although a decline of their CD10 and CD16 was observed (p < 0.01). No defect was found in the reactive oxygen species production and their apoptosis. The percentage of natural killer cells was in the normal range, whereas the percentages of CD8(+)NK and CD56(+)T lymphocytes were found to be high (p < 0.01). Although the absolute numbers of all lymphocyte subsets were low and showed a tendency for a gradual decrease in accordance with the disease progression, the most decreased absolute number was that of B lymphocytes, followed by CD4(+) T cells in the severe cases. The percentages of double-negative T cells; HLA-DR(+)CD3(+) and CD28(-)CD8(+) subsets were found to be significantly increased. Importantly, we demonstrated the increased baseline activation of caspase-3 and increased lymphocyte apoptosis. Conclusion We suggest that SARS-CoV-2 primarily affects the lymphocytes and not the innate cells. The increased baseline activation of Caspase-3 could make the COVID-19 lymphocytes more vulnerable to cell death. Therefore, this may interrupt the crosstalk between the adaptive and innate immune systems.
Keywords: apoptosis; caspase-3; COVID-19; immunophenotyping; oxidative burst; ACUTE RESPIRATORY SYNDROME; NK CELLS; RESPONSES; EXPRESSION; INDUCTION